Fatal outcome in the patient with the suspected ectopic pregnancy and diagnosed epithelioid trophoblastic tumor - Dobrosavljevic, Aleksandar Z; Nikolic, Branka; Maglić, Rastko; Petrović, Ivana; Stanković, Goran G (Vojnosanitetski pregled, 2021)
Abstract Introduction. Epithelioid trophoblastic tumor (EТТ) is an extremely rare form and unusual type of trophoblastic tumor. In 1998 ЕТТ became an independent entity because it possesses specific histological and immunohistochemical features which make it different from placental site tumor and choriocarcinoma. ЕТТ origins from intermediate trophoblast and it can overlap with the squamous cell carcinoma as per differential diagnosis. The relevant literature data suggest that surgical treatment is a treatment of choice for ETT considering that its response to chemotherapy is considerably poor. Case report. A 35-years-old patient G3 P2 came to an examination due to the low pelvic pain and absence of menstrual cycle. She reported that menstrual cycles were irregular during the past year. During the bimanual pelvic examination, a painful tumefaction being approximately 8 cm was palpated in the pouch of Douglas. The patient was operated on as being suspected for ectopic pregnancy when it was noticed that the aforementioned tumefaction was located retroperitoneally immediately against rectosigmoid part of the colon. After the histopathological analysis of the sample, in order to make the final diagnosis, the immunohistochemical test was performed and it found that this EТТ. Due to an inadequate response to administered chemotherapy, both resection of rectosigmoid colon with appurtenant tumor and left hepatectomy with salpingectomy on both sides were performed considering a possibility of gestational trophoblastic neoplasia (GTN) after ectopic pregnancy. Because of dehiscence of colorectal anastomosis, relaparotomy with colostomy bag fitting was performed. The patient died on the day 40 after surgical treatment due to hepatic insufficiency. Conclusion. In order to make as much adequate treatment method of ETT as possible, it is necessary to organize a team work with multidisciplinary approach. Surgical resection of the tumor is a primary method for treating ETT.